Depthwise separable convolution Unet for 3D seismic data interpolation - Jin, Zhenhui; Li, Xinze; Yang, Hui; Wu, Bangyu; Zhu, Xu (Frontiers in Earth Science, 2023)
In seismic exploration, dense and evenly spatial sampled seismic traces are crucial for successful implementation of most seismic data processing and interpretation algorithms. Recently, numerous seismic data reconstruction approaches based on deep learning have been presented. High dimension-based methods have the benefit of making full use of seismic signal at different perspectives. However, with the transformation of data dimension from low to high, the parameter capacity and computation cost of training deep neural network will increase significantly. In this paper, we introduce depthwise separable convolution instead of standard convolution to reduce the operation cost of Unet for 3D seismic data missing trace interpolation. The structural similarity (SSIM) and L_1 hybrid loss function and switchable normalization further improve the reconstruction performance of the network. The comparative experiments on synthetic and field seismic data show that depthwise separable convolution can effectively reduce the number of network parameters and computation intensity with the interpolation results comparable to the standard convolution results.